Enhancing dynamic resource management in decentralized federated learning for collaborative edge Internet of Things - Asma Aldrees; Ashit Kumar Dutta; Ahmed Emara; Sana Shahab; Zaffar Ahmed Shaikh; Yousef Ibrahim Daradkeh; Mohd Anjum (EURASIP Journal on Wireless Communications and Networking)
Abstract Dynamic situations and applications are supported by the diverse devices and communication technologies that constitute the Internet of Things concept. Despite this, communication backlogs are common due to rising network demand and insufficient resource allocation. This study provides a way to fix resource allocation problems using Mutable Resource Allocation and Distributed Federated Learning. Inadequacies and backlogs in resources are identified at the edge of the network. As part of this procedure, edge devices are assigned to link resources and users after independently determining which resources cannot be allocated and which shortcomings are linked with them. Adapting to demand and learning suggestions, this allocation is flexible. By classifying resources as sufficient or inadequate, the learning suggestions help avoid backlogs. This enables edge devices to choose between allocation and response, which improves network flexibility by prioritizing inadequate resource allocation. Accordingly, the recommendation factor periodically affects modifications to the edge connection and its interaction with the Internet of Things platform. The suggestion is particularly strong for situations with changing backlogs to ensure that subsequent resource allocations align with preference-based learning. Claiming to improve connection, services, and resource allocation while decreasing backlogs and allocation times, this approach is a hot commodity.